2014
DOI: 10.1007/s10103-014-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

The low level laser therapy (LLLT) operating in 660 nm reduce gene expression of inflammatory mediators in the experimental model of collagenase-induced rat tendinitis

Abstract: Tendinopathy is a common disease with a variety of treatments and therapies. Laser therapy appears as an alternative treatment. Here, we investigate the effects of laser irradiation in an experimental model of tendinitis induced by collagenase injection on rats' Achilles tendon, verifying its action in important inflammatory markers. Male Wistar rats were used and divided into five groups: control saline (C), non-treated tendinitis (NT) and tendinitis treated with sodium diclofenac (D) or laser (1 J) and (3 J)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…Low level laser therapy (LLLT) could reduce the expression of proinflammatory markers such as IL-6 and TNF- α in gene level [57]. In the cellular level, LLLT may increase collagen production [58], stimulate tenocyte proliferation [59], downregulate MMPs, decrease the capillary flow of neovascularization, and finally preserve the resistance and elasticity of tendon [60, 61].…”
Section: Treatmentmentioning
confidence: 99%
“…Low level laser therapy (LLLT) could reduce the expression of proinflammatory markers such as IL-6 and TNF- α in gene level [57]. In the cellular level, LLLT may increase collagen production [58], stimulate tenocyte proliferation [59], downregulate MMPs, decrease the capillary flow of neovascularization, and finally preserve the resistance and elasticity of tendon [60, 61].…”
Section: Treatmentmentioning
confidence: 99%
“…Regardless of aforementioned limitations, the included studies investigated several inflammatory mediators, such as pro-inflammatory mediators (interleukin-1 beta (IL-1b), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-a), cyclooxygenase-2 (COX-2), prostaglandin E2 (PGE2) and transforming growth factor beta (TGF-b)) (10)(11)19,21,(23)(24)27,33,35,39,(47)(48)(50)(51)(52)(53), as well as anti-inflammatory mediator [interleukin-10 (IL-10)] (21,30,48), involved in tendon repair or tendinitis condition. Other inflammatory mediator factors were also studied such as vascular endothelium growth factor (VEGF), metalloproteinase-1 matrix (MMP1), metalloproteinase-2 matrix (MMP-2), metalloproteinase-3 matrix (MMP-3), metalloproteinase-9 matrix (MMP-9), metalloproteinase-13 matrix (MMP13) and induced nitric oxide synthase (i-NOS) (10)(11)(28)(29)(34)(35)37,39,54) that contribute to the understanding of how PBMT can benefited tendon repair or tendinitis condition.…”
Section: Discussionmentioning
confidence: 99%
“…Some specific studies (18)(19)55) found that PBMT by LLLT or LED can stimulate the regeneration phase according to the dosimetry parameters (wavelength and energy). Casalechi et al (18) demonstrated a beneficial effect of PBMT by LED on the tendon regeneration process due to a significant decrease in the number of fibroblasts favoring the optimization of the tendon remodeling quality in all treated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLLT presents an activity on inflammation by modulation of pro‐ and anti‐inflammatory mediator expression, such as IL‐1β, IL‐6, TNF‐α, TGF‐β and IL‐10 . However, the possible explanation for LLLT cellular mechanisms that have driven to these results is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%